Novel Public-Key Encryption with Continuous Leakage Amplification. (15th October 2020) - Qiao, Zirui; Yang, Qiliang; Zhou, Yanwei; Xia, Zhe; Zhang, Mingwu
Abstract: Leakage of private information, such as the secret keys, has become a threat to the security of computing systems. It has become a common requirement that cryptographic schemes should withstand various leakage attacks, including the continuous leakage attacks. Although some research progresses have been made toward this area, there are still some unsolved issues. In the literature, the public-key encryption (PKE) constructions with (continuous) leakage resilience normally require the upper bound of leakage to be fixed. However, in many real-world applications, this requirement cannot provide sufficient protection against leakage attacks. In order to mitigate these problems, this paper demonstrates how to design a leakage amplified PKE scheme with continuous leakage resilience and chosen-plaintext attacks security. In our proposed PKE scheme, the leakage parameter can have an arbitrary length. Moreover, the length of permitted leakage in our scheme can be flexibly adjusted according to the leakage requirements of application environment. Its security is formally proved under the classic static assumption.